1998
DOI: 10.1111/j.1745-459x.1998.tb00093.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature, Fat Content and Package Material on the Sensory Shelf‐life of a Commercial Mayonnaise

Abstract: Mayonnaise is microbiologically stable, thus its shelf‐life is determined by the change in its sensory properties, mainly flavor changes due to oxidative rancidity of its main component, oil. The effect of storage temperature, fat content and type of package on the shelf‐life of a commercial mayonnaise was studied. Sensory descriptors with corresponding references are presented. The sensory descriptors which varied with storage time were: total aroma, and for flavor: egg, oily and oxidized. Rate of oxidized fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
4
5
0
Order By: Relevance
“…Studies showed that type of package (jar or pouch) do not have an effect on changes during M A N U S C R I P T A C C E P T E D storage time while package size influence aroma of mayonnaise (Martinez, Mucci, Cruz, Hough, & Sanchez, 1998). Reducing oxygen concentration (minimizing headspace in the container or packaging under vacuum or nitrogen) can reduce the oxidation rate in mayonnaise (Hsieh, 1990;Hsieh & Regenstein, 1991).…”
Section: Packagingmentioning
confidence: 99%
“…Studies showed that type of package (jar or pouch) do not have an effect on changes during M A N U S C R I P T A C C E P T E D storage time while package size influence aroma of mayonnaise (Martinez, Mucci, Cruz, Hough, & Sanchez, 1998). Reducing oxygen concentration (minimizing headspace in the container or packaging under vacuum or nitrogen) can reduce the oxidation rate in mayonnaise (Hsieh, 1990;Hsieh & Regenstein, 1991).…”
Section: Packagingmentioning
confidence: 99%
“…the attribute that has the highest impact on the quality of the milk, or shows the most change over the shortest time period. This is a very hard decision to make, especially when sensory variables are included in the study (Curia & Hough, 2009;Hough et al, 2002;Martínez, Mucci, Santa Cruz, Hough, & Sanchez, 1998). The multivariate accelerated shelf-life approach includes all the attributes that show change over time and gives a single acceleration coefficient (Labuza & Schmidl, 1985;Pedro & Ferreira, 2006).…”
Section: Milk Composition and Microbiological Qualitymentioning
confidence: 99%
“…Sensory shelf-life tests are done using different approaches after varying product storage conditions and study duration. Common approaches include descriptive tests to measure quality changes 8 and hedonic testing to evaluate the impact of quality changes in consumers' acceptability or preference. 9 Acceptance test or preference tests have also been used 10 to estimate shelf-life.…”
Section: Introductionmentioning
confidence: 99%